Digital Transformation at Forefront: Impact of Digital Orientation, Capabilities, and IT-Business Synergy on Higher Education Institutions Performance - Renta, Muhammad Prans Panca; Ali, Syaiful (The Indonesian Journal of Accounting Research, 2025)
This study investigates the impact of digital orientation, digital capabilities, and IT-business synergies on digital transformation. Additionally, it explores how these three variables influence higher education institutions' performance, using digital transformation as a mediating factor. This research was conducted based on the reality gap between the demands of adapting and making changes or transforming towards digital and higher education readiness. This research was conducted during the COVID-19 pandemic, a phenomenon that has triggered digital transformation. The object of this research is higher education institutions. This research adds IT factors and business synergy, which means the business in this research is educational programs and services in higher education. Data was gathered through an online survey of higher education institutions across Indonesia. The number of questionnaires processed was 124. The data was then analyzed using the SEM-PLS method. The study's findings reveal that digital orientation, digital capabilities, and IT-business synergy all significantly and positively impact digital transformation. Furthermore, digital transformation mediates the influence of digital orientation, digital capabilities, and IT-business synergy on collegiate performance. This research provides several things that need to be paid more attention to by higher education institutions when it comes to the findings in this study. First, higher education institutions must write clearly in their policies. Second, higher education institutions do not only focus on human resources but must also be supported by qualified technological resources. Third, higher education institutions must consider the involvement of the teaching team in IT projects.